MINI TINJAUAN LITERATUR PEMANFAATAN APLIKASI PHOTOMATH UNTUK BERPIKIR KOMPUTASI SISWA - Mukhlida Khofipah Hasibuan; Yahfizham (CV. Adiba Aisha Amira, 2025)
The advancement of digital technology today has driven various innovations in the world of education, especially in mathematics learning. One of the widely used applications is Photomath, which is able to explain mathematical concepts and present the steps of solving them visually. This study is intended to evaluate the use of the Photomath application in strengthening students' computational thinking skills. Using the Systematic Literature Review (SLR) method, 12 relevant articles were analyzed in depth. The results show that Photomath helps students understand mathematical concepts through structured problem solving. This application also trains computational thinking skills such as decomposition, pattern identification, and algorithms. With teacher assistance, Photomath can be an effective learning medium.